A desiccant evaporative air conditioning performance improvement using heat pipe heat exchanger as a heat recovery device - Adel Alblawi (Case Studies in Thermal Engineering)
Desiccant evaporative systems represent promising alternatives to conventional air conditioners adopted for hot and humid climatic. Many desiccants augmented evaporative cooling systems have been reported in the literature. These systems include ventilation or conventional cycle, recirculation cycle, Dunkle cycle and regenerative heat exchanger cycle. The ventilation cycle is the earliest and probably the most commonly used in desiccant evaporative systems. In the present research, three new configurations are suggested and compared with the Traditional ventilation desiccant evaporative cooling system under different desiccants while inlet air temperature (28–46 °C) and air humidity ratio (0.01–0.02kgwv/kgda). A simulation model has been established and validated with the available experimental data in the literature of the traditional cycle. The comparison confirms that the assessment of the simulation model agrees with the experimental data and the obtained average errors of 1.74 % for temperature and 2.1 % for humidity ratio at the cycle state points. The energetic and exergetic analysis revealed that the suggested sys1 has the same performance as the traditional system while the suggested sys3 has higher thermal coefficient of performance (COPth), exergy efficiency and air handling coefficient of performance (COPD) than that of the other suggested systems. The COPth of the traditional system changed from 0.442 to 0.3 while for suggested sys3 it varied from 0.664 to 0.552 as an inlet temperature changed from 28 to 46 °C. However, as the inlet air humidity ratio increases from 0.01 to 0.02 kgwv/kgda the COPth of the traditional system decreases from 0.55 to 0.26 while for suggested sys3 decreases from 0.813 to 0.483. The system which uses the heat pipe heat exchanger and direct indirect evaporative cooler after the rotating heat exchanger (suggested sys3) has higher performance than that of the other suggested systems from energetic and exergetic points of view.